Atherosclerosis and the Hypercholesterolemic AGE–RAGE Axis - McNair, Erick; Qureshi, Mabood; Prasad, Kailash; Pearce, Colin (International Journal of Angiology, 2016)
Background Interaction of advanced glycation end products (AGE) with the receptor for advanced glycation end products (RAGE) has been implicated in the pathogenesis of atherosclerosis. Soluble receptors for advanced glycation end products (sRAGE) act as a decoy for AGE by competing with RAGE and suppressing developing atherosclerosis. Hypercholesterolemia and the oxidative stress are known factors involved in atherosclerosis. High-density lipoprotein cholesterol (HDL-C) is known to exert a protective effect against the development of atherosclerosis.We hypothesize that hypercholesterolemia-induced atherosclerosis may be mediated through the AGE–RAGE axis.Objectives Two objectives to be determined are: (1) if hypercholesterolemia is positively correlated with serum AGE, AGE/sRAGE, and malondialdehyde (MDA: a marker for oxidative stress) and (2) if the protective effect of HDL-C is positively associated with serum sRAGE and negatively correlated with the levels of AGE and AGE/sRAGE.Methods Measurement of serum lipid levels from 100 patients allowed the separation into two groups (hypercholesterolemic and normocholesterolemic). Measurements of serum levels of AGE, sRAGE, and MDA were performed.Results Serum levels of sRAGE were lower, while the levels of AGE and AGE/sRAGE were higher in hypercholesterolemic subjects as compared with normocholesterolemic subjects. sRAGE levels are positively correlated with HDL, while they are negatively correlated with low-density lipoprotein, triglycerides, total cholesterol, and MDA in hypercholesterolemic subjects.Conclusions Hypercholesterolemia is positively correlated with serum AGE, AGE/sRAGE, and MDA. The effect of HDL-C may be due to increases in sRAGE and decreases in the levels of AGE and AGE/sRAGE. Hypercholesterolemia-induced atherosclerosis may be mediated through the AGE–RAGE axis; however, more research must be conducted.
Keywords: atherosclerosis; advanced glycation end product; hypercholesterolemia; oxidative stress; coronary artery